Matrix Metalloproteinase-9 Overexpression Regulates Hippocampal Synaptic Plasticity and Decreases Alcohol Consumption and Preference in Mice - Yin, Li- Tian; Xie, Xiao-Yan; Xue, Lin-Yuan; Yang, Xiao- Rong; Jia, Juan; Zhang, Yu; Zhang, Ce (Neurochemical research, 2020)
Brain matrix metalloproteinases (MMPs) have been recently implicated in alcohol addiction; however, the molecular mechanisms remain poorly understood. Matrix metalloproteinase-9 (MMP-9), an extrasynaptic protease, is the best described MMP that is thought to regulate addictive behavior. In the present study, the effect of MMP-9 overexpression on hippocampal neuron plasticity and alcoholic behavior was assessed in spontaneous alcohol drinking mice. Two-bottle choice model showed that the overexpression of MMP-9 in the hippocampus developed by adeno-associated virus (AAV) could decrease alcohol consumption and preference, but did not affect taste preference, which was tested using saccharin or quinine solutions. Dendritic spines number of hippocampal neurons was observed by Golgi staining. Compared with the alcohol treatment group, the density of dendritic spines in the hippocampus of alcohol drinking mice was decreased in alcohol + MMP-9 group. Western blot analysis indicated that GluN1 expression in the hippocampus of alcohol drinking group was lower than that in the control group, while the expression of GluN1 was increased in MMP-9 overexpressing mice. MMP-9 also regulated the depolymerization of actin filaments, which induced behavioral changes in mice. Taken together, overexpression of MMP-9 in the hippocampal neurons of mice resulted in decreased dendritic spine density and F-actin/G-actin ratio, which might be the crucial reason for the significant decrease in alcohol consumption in alcohol drinking mice. MMP-9 might be considered as a novel target studying the molecular mechanism of alcohol drinking.